(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
ADHD is a neurobiological disorder characterized by inattention, impulsivity and motor hyperactivity. Generally, a child with ADHD, it’s always not meta-cognitive, inattentive to the procedure implementation to resolve any problem, and it is not sufficiently strategic. Physical activity is for the person with ADHD, the celebration of what it does and what it can be, allowing in this way, a natural inclusion of training skills, knowledge and personal resources.